A Correlational study between teacher made schema test and secondary school pupils’ performance in essay writing (2010)
One area of language learning that constitutes great concern to secondary school pupils is writing. A lot of reasons has been given by various researchers as the causes of this weakness in most secondary school pupils. This study investigated the role of schema on pupils’ performance in essay writing. A total number of one hundred and two (102) pupils’ from two co-educational institutions was randomly selected for the study. The instruments used were Test on Pupils’ Schema (TOPS) and Test on Writing (TOW). Two research questions were used in the study. Findings revealed that there is a significant correlation between pupils’ schemata and writing ability. The study recommends that pupils’ schemata be given serious attention by stakeholders in education and that good methods of teaching essay writing should be adopted by teachers.